Representasi Tradisi Dalam Film "Sedekah Ka Bumi" Produksi Watchdoc Documentary - Komaria; Sumaina Duku; Anang Walian (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2024)
Indonesia is a country that has various cultures that develop in society. Culture is a habit that is passed down from one generation to another, discussing culture is certainly a very interesting thing, seeing the many traditions that each region has. The development of traditions can be found in various traditional rituals in each region. We can see one of these traditions in the documentary entitled "Sedekah Ka Bumi" which is the work of Rendi Dwi Julianto. This documentary film tells the tradition of making offerings to the earth which is held every year by the residents of Urug village, Bogor district, West Java. The aim of this research is to find out how "Tradition is represented in the film "Sedekah Ka Bumi" produced by watchdoc documentary". The theory used by the researcher is Roland Barthes' Semiotic Theory, the data collection technique is Observation, Documentation and Literature Study, the data analysis technique is carried out using reduction. data, presenting data and drawing conclusions. The results of this research are 12 scenes that show a tradition which can be seen through the signs and meanings in the film. This film shows a series of earth alms ceremonies for the Urug village community which are carried out to ask for safety and blessings from Allah SWT, especially in farming or before planting rice.